UMA SEQUÊNCIA DE ENSINO PARA O ESTUDO DE INTEGRAIS DUPLAS - Fontoura, Leandro Ribeiro (2016)
This dissertation has the aim to investigate the contribution from the application of a didactic sequence elaborated in accordance with the assumptions of Didactic Engineering and the usage of a computer application from software Maple for teaching and learning of the double integrals subject for Mathematics Degree students. The theoretical background for analysing the results was based in the Tall and Vinner (1981) theory about the image concept and definition concept and it was used the Domingos (2003) categorization in order to classify the students in three different levels of image concept: incipient image concept, instrumental image concept and relational image concept. From the preliminary studies resulted from the didactic books analysis and from results of the application of a diagnostic test, it was elaborated one didactic sequence, compounded by four activities to build the Double Integral concept and used it in applications related to volume calculations of geometric solids. The data for analyses were obtained through participant observation from the researcher’s field logbook and from documents produced by students. Participated in this research Mathematics Degree students enrolled in the course Differential and Integral Calculus IV. The results shown that the proposed didactic sequence and the usage of a computer application programmed with the software Maple facilitated the formation of image concepts about the Double Integrals subject and helped students to calculate the volume of geometric solids.